2021
DOI: 10.1186/s13643-020-01568-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for depression in children and adolescents: a protocol for a systematic review update

Abstract: Background Major depressive disorder is common, debilitating, and affects feelings, thoughts, mood, and behaviors. Childhood and adolescence are critical periods for the development of depression and adolescence is marked by an increased incidence of mental health disorders. This protocol outlines the planned scope and methods for a systematic review update that will evaluate the benefits and harms of screening for depression in children and adolescents. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
0
10
0
2
Order By: Relevance
“…This may result of a better perception to understand what is happening around them due to increase in their mental capacity with age. Environmental factors such as school-related problems, difficulties in relationships with peers, learning difficulties, decreased sleep quality, tendency to unhealthy diet, increased screen time may also be risk factors for increased frequency of depression during adolescence (23). It has been reported that children with long-term health problems have a higher risk for depression (24).…”
Section: Discussionmentioning
confidence: 99%
“…This may result of a better perception to understand what is happening around them due to increase in their mental capacity with age. Environmental factors such as school-related problems, difficulties in relationships with peers, learning difficulties, decreased sleep quality, tendency to unhealthy diet, increased screen time may also be risk factors for increased frequency of depression during adolescence (23). It has been reported that children with long-term health problems have a higher risk for depression (24).…”
Section: Discussionmentioning
confidence: 99%
“…A protocol for the review was published [ 44 ] and registered with the PROSPERO database (CRD42020150373) and was made available on the Open Science Framework ( https://osf.io/h5nbp/ ). Details on how eligibility criteria and outcomes were determined can be found in the protocol [ 44 ]. Any materials used in the review can be found on the Open Science Framework.…”
Section: Methodsmentioning
confidence: 99%
“…As described in our study protocol [ 44 ], we planned to extract data from the included studies, perform risk of bias assessments, conduct analyses, and assess the certainty of the evidence if any studies met our inclusion criteria. However, despite our comprehensive search strategy, we were unable to identify any eligible studies on depression screening in children and adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, depression is one of the most common mental health problems in children and adolescents and mainly manifests as a persistent decline in academic performance, feelings of worthlessness, difficulty in making friends, and poor sleep quality [ 5 , 6 ]. Depression is very common among adolescents and affects adolescents’ interpersonal relationships, academic performance, and hobbies as well as their physical and mental health; severe depression may even be life-threatening [ 7 ]. Suicide is the third leading cause of death among children and adolescents, and depression is the leading cause of suicide among adolescents.…”
Section: Introductionmentioning
confidence: 99%